Soil Engineering: Testing, Design, and Remediation - Chen, Fu Hua (CRC Press, 2009)
In the last forty years, at least fifty books have been written on the subject of soil mechanics, most of them textbooks. Only a few touch on practical applications. Soil Engineering: Testing, Design, and Remediation supplies the information needed to fill the gap between textbook learning and practical know-how.